Adult-Onset Still Disease Presenting With Dermatomyositis-Like Persistent Pruritic Lesions. (November 2019) - Qiao, Jianjun; Pan, Yunlei; Li, Sheng; Tang, Shunli; Zheng, Siting; Zhu, Dingxian; Sun, Chuanyin; Fang, Hong
Abstract : Abstract: Adult-onset Still disease (AOSD) is a rare autoinflammatory condition. The presence of an evanescent, salmon-pink, nonpruritic rash is one of the major diagnostic criteria for the disease. The rash occurs with fever and subsides with defervescence. The presence of dyskeratotic keratinocytes in the upper one-third layer of the epidermis is a distinctive histopathological feature of persistent pruritic lesions associated with AOSD. Here, we report 2 cases of AOSD characterized by persistent pruritic lesions resembling those observed in dermatomyositis. Identifying the clinical and histopathological manifestation of the cutaneous lesions is essential for the early diagnosis of AOSD and for differentiating this condition from those presenting with dyskeratotic cells in the epidermis.